2019
DOI: 10.1002/asi.24256
|View full text |Cite
|
Sign up to set email alerts
|

What Is Known About the Impact of Impairments on Information Seeking and Searching?

Abstract: Information seeking and access are essential for users in all walks of life, from addressing personal needs such as finding flights to locating information needed to complete work tasks. Over the past decade or so, the general needs of people with impairments have increasingly been recognized as something to be addressed, an issue embedded both in international treaties and in state legislation. The same tendency can be found in research, where a growing number of user studies including people with impairments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 76 publications
1
32
0
Order By: Relevance
“…The serial nature of the screen reader output reduces the speed at which the VI web users access the information during the exploration stage. Some studies [1,20] have suggested providing VI web users with an overview of the search results, and Berget and MacFarlane [21] stated that user interface design is a clear issue for VI users for navigating search results. However, to the best of our knowledge, no study has yet suggested a mechanism to provide such an overview and change user interface design to enable easy navigation through the search results.…”
Section: Motivation and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serial nature of the screen reader output reduces the speed at which the VI web users access the information during the exploration stage. Some studies [1,20] have suggested providing VI web users with an overview of the search results, and Berget and MacFarlane [21] stated that user interface design is a clear issue for VI users for navigating search results. However, to the best of our knowledge, no study has yet suggested a mechanism to provide such an overview and change user interface design to enable easy navigation through the search results.…”
Section: Motivation and Research Questionsmentioning
confidence: 99%
“…Furthermore, this process may be repeated if the desired goals are not met. Berget and MacFarlane's [21] literature review showed that interface design impacts the navigating and evaluating search results that are part of the search process.…”
Section: Information-seeking Processmentioning
confidence: 99%
“…The starting point of this paper was that few studies of people with impairments include user models (Berget and MacFarlane, 2020). Moreover, it has been claimed that existing models are not sufficient for describing characteristics specifically connected with the various impairments (Beverley et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These models have later been applied extensively (Wilson, 1999). Over the last decade, attention has increasingly been directed towards the information seeking and searching of users with impairments (Hill, 2013, Berget andMacFarlane, 2020). Studies on users with impairments, however, rarely include any models of information seeking and searching (Berget and MacFarlane, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, digital libraries and online search systems can be suitable alternatives to visiting a physical library. However, online information searching can pose several barriers for people with disabilities, such as poorly designed search user interfaces, inaccessible information and incompatibility with assistive technology (Berget & MacFarlane, 2019). Many users with disabilities are therefore excluded from online health information, which can contribute to health disparities.…”
Section: Introductionmentioning
confidence: 99%